The Role of the Community in Preventing Stunting Through the Bintan Regency DP3KB Family Assistance Team (TPK) Program - Rahmawaty, Ratih; Selselviana, Ella; Suryaningsih (Jurnal Pengabdian Masyarakat Bestari, 2024)
Stunting is a chronic nutritional problem characterized by a child's height being below the expected standard for their age. Stunting can have negative impacts on children's physical and mental development. This community service aims to increase the role of the community in preventing stunting through the Family Support Group (TPK) program of the Bintan DP3KB. The results of this community service activity show that the active role of the community in preventing stunting is essential. Through an approach that includes socialization, direct support, skill development, and continuous monitoring, the community can be better educated and more actively involved in ensuring adequate nutrition for healthy living and optimal child development.